(untitled) (Progressive Agriculture, 2013)
The research was conducted to study the effect of heat stress on behavior, some physiological and blood parameters with nine goats of almost similar in age, sex and weight into three groups. Three groups were divided as zero hour (T0), four hours (T4) and eight hours (T8) heat exposure. Temperaturehumidity index (THI) value was calculated as 28.17 which indicate the experimental animals were in extreme severe heat stress. Skin and rectal temperature had no significant differences among the treatment groups but respiration/panting and pulse rate were increased with the increased of heat stress from T0 to T8 group (P<0.01). Significant difference was found in standing time and lying time (P<0.01) in experimental groups. There were significant changes (P<0.01) in number of urination and defecation per hour but no significant changes was found in duration per urination in heat treated groups. The amount of RBC, PCV%, Hb%, WBC were increased with the increased of heat stress (P<0.01). Neutrophil, eosinophil, lymphocyte and monocyte numbers increased significantly (P<0.01) in heat treated groups. It can be concluded that heat stress had significant changes on some behavioral, physiological and blood parameters of goat. DOI: http://dx.doi.org/10.3329/pa.v22i1-2.16465 Progress. Agric. 22(1 & 2): 37 - 45, 2011